A bioreactor-based platform for investigating the early response of human periodontal ligament stem cells to intermittent mechanical stretching - Putame, Giovanni; Masante, Beatrice; Tosini, Marta; Lugas, Andrea T.; Roato, Ilaria; Terzini, Mara; Audenino, Alberto L.; Mussano, Federico; Massai, Diana (Frontiers in Bioengineering and Biotechnology, 2025)
During development and daily activities, biological tissues are frequently exposed to mechanical stimuli, which are crucial for tissue maintenance and regeneration. The periodontal ligament (PDL), which connects the tooth root to the alveolar bone of the jaw, is among the tissues most exposed to mechanical loading and has recently received increasing attention due to the rising prevalence of periodontitis, a chronic inflammatory disease that leads to the progressive destruction of tooth-supporting structures. Understanding the mechanobiology of PDL could be essential for guiding effective regenerative strategies. To address this, a bioreactor-based platform for applying controlled stretch stimulation to adherent cells was developed, and the early biological response of human primary PDL stem cells (hPDLSCs) to different intermittent stretching protocols was investigated. Furthermore, to correlate the mechanical stimulus applied to the cells with their biological response, a detailed characterization of the substrate deformation was performed. The platform integrates an existing stretch bioreactor, updated to enable automated alternation of constant and dynamic stretching conditions without user intervention, with a custom-designed polydimethylsiloxane (PDMS) deformable substrate, whose geometry was optimized for ensuring the most uniform strain distribution. The mechanical behavior of the substrate was accurately characterized via finite element analyses and experimental tensile tests combined with digital image correlation analyses. This revealed slight discrepancies between the imposed and actual strain experienced by the substrate and assumed to be provided to the adherent cells. Preliminary biological experiments showed distinct responses in hPDLSCs and adipose-tissue derived stem cells (ASCs) exposed to intermittent stretching: hPDLSCs exhibited upregulation of osteogenic gene expression, while ASCs showed no significant changes under identical conditions. Furthermore, hPDLSCs were exposed to three different intermittent stretching protocols. Increasing the total daily cyclic stretch exposure enhanced the hPDLSCs early response, including alignment along the stretch direction and upregulation of both osteogenic and PDL-related gene expression. Overall, this study confirmed the suitability of the proposed platform for investigating the effects of controlled stretching on mechanosensitive cells such as hPDLSCs and provided valuable insights into their early response to intermittent stretching protocols.